Sensitivity of Occupant Response Subject to Prescribed Corridors for Impact Testing. (1996) - Crandall, J.R.; Pilkey, W.D.; Kang, W.; Bass, C.R.
Abstract : A technology to study the sensitivity of impact responses to prescribed test conditions is presented. Motor vehicle impacts are used to illustrate the principles of this sensitivity technology. Impact conditions are regulated by specifying either a corridor for the acceleration time history or other test parameters such as velocity change, static crush distance, and pulse duration. By combining a time domain constrained optimization method and a multirigid body dynamics simulator, the upper and lower bounds of occupant responses subject to the regulated corridors were obtained. It was found that these prescribed corridors may be either so wide as to allow extreme variations in occupant response or so narrow that they are physically unrealizable in the laboratory test environment. A new corridor based on specifications for the test parameters of acceleration, velocity. crush distance, and duration for frontal vehicle impacts is given.